Alat Permainan Edukatif Sebagai Sumber Dan Media Pembelajaran Anak Usia Dini - Fatimah, Friska Nur; Afifah, Hilyatul Ulya Najwa; Auliani, Rizky; Larasati, Sekar Ayu (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2023)
This publication discusses the history and distribution of early childhood education using educational play technology. The resources found in educational games can aid kids in growing intellectually, physically, socially, emotionally, morally, and spiritually, as well as in the arts. With the use of these play toys, a teacher will find it simpler to instruct early childhood learning materials. A descriptive qualitative literature review was employed as the research methodology in this study. employed in this study as a method of studying literature. This study aims to help kids grow in all ways by using educational game technology as a source and a vehicle for learning.